El 11 de febrero, entre el mito y la nostalgia. La conmemoración de la Primera República española por los republicanos durante la Restauración - Oscar Anchorena Morales (Cahiers de Civilisation Espagnole Contemporaine)
The democratic experience of 1873 in Spain was, in a short space of time, intense and conflictive. However, the destruction of the Republic by force did not imply its abandonment by republicanism, which from then on cultivated its memory and incorporated it as another element in its fight against the Bourbon monarchy. For many years, 11 February, the day of the proclamation of the First Republic, was the main common identity myth of republicanism, although it coexisted with other anniversaries of democratic and popular history. Its annual commemoration was the scene of symbols and historical appropriations, legends and heroes, innovation in mobilisation tactics and programmes, and struggles to define memory and lead republican political action. The study of 11 February provides an insight into the political culture, the strategic dilemmas and the struggles with the authorities that the Republican forces experienced during the half-century of the Restoration regime.